2023
DOI: 10.1136/jnnp-2021-328323
|View full text |Cite
|
Sign up to set email alerts
|

Axonal degeneration in chemotherapy-induced peripheral neurotoxicity: clinical and experimental evidence

Abstract: Multiple pathological mechanisms are involved in the development of chemotherapy-induced peripheral neurotoxicity (CIPN). Recent work has provided insights into the molecular mechanisms underlying chemotherapy-induced axonal degeneration. This review integrates evidence from preclinical and clinical work on the onset, progression and outcome of axonal degeneration in CIPN. We review likely triggers of axonal degeneration in CIPN and highlight evidence of molecular pathways involved in axonal degeneration and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 107 publications
(207 reference statements)
1
10
0
Order By: Relevance
“…One of the major issues in designing a preventive clinical trial in CIPN is enrolling patients who will actually develop peripheral neuropathy, since not all patients will experience CIPN and, even if neurotoxicity ensues, its severity can vary. 4,7,10,28 We already proposed the longitudinal monitoring of the dorsal sural nerve at mid-treatment to detect patients at higher risk to develop neuropathy in a clinical setting, 6 but it would be far more valuable to have a tool that even more precociously can detect changes predictive of axonal damage, as NET was demonstrated to be doing in our preclinical proof-of-concept study. Furthermore, differently from serum biomarkers such as neurofilament light chain (NfL) levels, 8 Thus, it could be suggested that NET should be further explored as a precious link between bench and bedside for research purposes: in fact, at bench side, all hypotheses just indirectly inferred via NET on axonal damage can be directly confirmed via histopathology and biomolecular techniques.…”
Section: Ncsmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the major issues in designing a preventive clinical trial in CIPN is enrolling patients who will actually develop peripheral neuropathy, since not all patients will experience CIPN and, even if neurotoxicity ensues, its severity can vary. 4,7,10,28 We already proposed the longitudinal monitoring of the dorsal sural nerve at mid-treatment to detect patients at higher risk to develop neuropathy in a clinical setting, 6 but it would be far more valuable to have a tool that even more precociously can detect changes predictive of axonal damage, as NET was demonstrated to be doing in our preclinical proof-of-concept study. Furthermore, differently from serum biomarkers such as neurofilament light chain (NfL) levels, 8 Thus, it could be suggested that NET should be further explored as a precious link between bench and bedside for research purposes: in fact, at bench side, all hypotheses just indirectly inferred via NET on axonal damage can be directly confirmed via histopathology and biomolecular techniques.…”
Section: Ncsmentioning
confidence: 99%
“…19,22,31,38 In part, this unmet clinical and scientific need is due to an incomplete understanding of axonal damage mechanisms related to different anticancer drugs. 28 Therefore, it is crucial to have robust preclinical models addressing pathogenetic mechanisms. 15 In this regard in vivo models are pivotal and it is mandatory to use translational methods to promptly transfer data from bench to bedside and vice versa; nerve conduction studies (NCS) are quite a relevant option since they can be similarly performed at a preclinical and clinical level in CIPN.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different antineoplastic agents target distinct components of the PNS including apoptosis of DRG neuronal cell bodies, changes in axonal transport pathways, mitochondrial dysfunction, and abnormalities in Ca 2+ regulation systems as well as axonal membrane ion channels. 12,13 Accordingly, its clinical features are dependent on the type of the agent involved, ranging from pure sensory axonal to sensory-motor neuropathies, with or without pain and autonomic impairment. 14 Its clinical phenotype is mainly characterized by paresthesias and dysesthesias in peripheral limbs, numbness, ataxia, tingling, decreased sense of vibration and impaired deep tendon reflexes.…”
Section: Introductionmentioning
confidence: 99%